INNOVATION IN FACILITY AND INFRASTRUCTURE MANAGEMENT (SI) TO UPGRADE CHAIYAPHUM RAJABHAT UNIVERSITY TO GREEN UNIVERSITY - Sichaiwong, Pramuk; Sangsida, Worachate; Suthandee, Chartnarongsak; Tonglor, Nattawut; Sinton, Samart (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research are to 1) develop the body of knowledge Technology and innovation in locations and infrastructure appropriate to the Chaiyaphum Rajabhat University context. To become a green university 2) Develop a management model for locations and infrastructure of Chaiyaphum Rajabhat University to become a green university and 3) Transfer technology and innovations for management of locations and infrastructure of green university The sample group used in the research included students in the service area, students, personnel of Chaiyaphum Rajabhat University and representatives of villagers around Chaiyaphum Rajabhat University, totaling 225 people. Tools used in the research included questionnaires and interviews. Statistics used in data analysis include basic statistics, data analysis. From the questionnaire, including the mean and standard deviation, and qualitative data were analyzed from content analysis. The research results were found: 1) Results of the study of student representatives’ satisfaction with the development of Chaiyaphum Rajabhat University. Towards becoming a green university overall is at a high level. When considering each aspect, it was found that the aspect of landscape improvement was the most satisfying. Followed by curriculum and research and supporting activities towards becoming a green university, respectively. The building and facility aspect was the least satisfied. 2) Results of the development of the facility and infrastructure management model. of Chaiyaphum Rajabhat University To become a green university, consisting of 1) learning resources and study and study innovative energy technology Community and conservation careers Restoring natural resources. 2) Activity area for students and staff to participate in activities. 3) Improving the stadium by maintaining the original stadium to be ready for use and in the process of constructing a standard swimming pool as a recreation area for students and staff, and 4) determining green zones and planting forests Added to be an area for conservation and restoration of natural resources. 3) Results of technology transfer and innovation in management of locations and infrastructure of the Green University. Provide training and transfer knowledge and innovation to target groups. Including students and people around the university have 8 learning bases consisting of 1) Biochar or Biochar burning base 2) Biogas or Biomethane production base 3) Distribution base. Water with solar cells or solar panels (Solar Cell) 4) Non-recycled organic fertilizer production base 5) Bio-fermented water production base 6) Azolla culture base 7) Closed underground water bank base and 8) Base smart greenhouse.